(untitled) (University of Khartoum Engineering Journal, 2022)
This paper presents the application of PSS with based damping controller FACTS device and describes a coordinated tuning of parameters. The FACTS device considered here is Static Var Compensator (SVC). The method proposed to optimize the controller parameters is Particle Swarm Optimization (PSO) algorithm. The Single Machine Infinite Bus (SMIB) with PSS and SVC-based damping controller is selected as a case study system. In order to evaluate the effectiveness of these controllers, eigenvalues analysis and nonlinear simulation of this system are carried out under different loading conditions. The simulation results shows that PSS coordinated with SVC based stabilizer have outstanding fast damping of low frequency power system oscillations.